Efektivitas Kombinasi Ekstrak Temulawak, Jahe, Kedelai, dan Kulit Udang Dibandingkan Dengan Natrium Diklofenak Pada Pasien Osteoartritis - , DEWI SURYANINGSIH, Dr. dr. Nyoman Kertia, Sp.PD., K-R ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Indonesian herbal plants are believed to have great benefits for the development of medicine and the pharmaceutical industry in Indonesia. Temulawa, ginger, soy, and shrimps shells that used in the formula-shaped of a capsule formula can be used as a treatment for osteoarthritis conditions, but current clinical trials is still a bit done. This study was aimed to investigated the effect of the combination of the test capsule compared with diclofenac sodium 25 mg for its effectiveness in relieving pain and reducing joint fluid leukocytes of osteoarthritis disease. The study design was a prospective randomized open blinded end evaluation (PROBE). Forty-seven subjects involved in this study were divided randomly into two groups (test group and the diclofenac sodium group). The test group was given combination therapy of 100 mg temulawak extract, ginger 100 mg, 50 mg soy and 50 mg shrimp shell, three times a day for two weeks, while the control group was given 25 mg of diclofenac sodium tablets three times daily for two weeks. Examinations performed before and after 2 weeks of therapy to assess the numbers of VAS (Visual Analogue Scale) in the case of joint pain and assess the number of leukocyte in the joint fluid on patients with osteoarthritis of the knee. The measurement results VAS scores in each treatment group were significantly decreased by a margin decline of -17.31 ± 15.41 (p <0,05). Decrease in VAS score was not significantly different between the two treatment groups (p> 0,05). Measurement results to the decline in the numbers of leukocytes in the knee joint fluid test capsule group showed a decrease by a margin of -38.59 ± 161.21 (p> 0,05). While measuring the decrease in the number of leukocytes in the knee joint diclofenac group experienced an increase of 17.56 ± 99.59 (p> 0,05). Result the two groups showed no significant difference in terms of decreasing the number of leukocytes joints with p = 0.273 (p> 0,05). The combination of temulawak extract capsules 100 mg, 100 mg ginger, soy 50 mg, and 50 mg shells are taken 3 times a day can reduce the level of pain and joint fluid leukocyte numbers in patients with knee osteoarthritis significantly in treatment for 2 weeks.